Reactivation of Coccidioides immitis in a Prosthetic Knee after Initiation of Chemotherapy - Ciochetto, Zachary; Georgen, Maria; Hadro, Adam; Jurkowski, Lauren; Ridolfi, Kimberly; Wooldridge, Adam; Gundacker, Nathan; Haque, Javeria (Case Reports in Hematology, 2021)
Coccidioides is an endemic fungus in the Southwestern United States and Central and South America. Coccidioidomycosis primary infections are typically of the lung with an asymptomatic or self-limiting course. Some infections disseminate to other parts of the body and a few can remain latent for many years. Reactivation of latent fungal disease can occur following an insult to the host immune system. Here, we describe a case of a 76-year-old Caucasian male patient who moved from California to Wisconsin with a history of coccidioidomycosis infection of the left knee that reactivated decades later in his prosthetic knee shortly after being initiated on ibrutinib (Imbruvica), a Bruton tyrosine kinase (BTK) inhibitor, for chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). There have been some case reports regarding coccidioidomycosis infections after initiating ibrutinib therapy but none with a 50 year latency period before reactivation. Readers will learn the immunological effects of ibrutinib on the hosts’ innate and adaptive immunity and its role in putting the host at risk for invasive fungal infections. We also review the literature and data on treatment regimens and recommendations based on current guidelines.